Factors that influence frontline employee behavior towards guest satisfaction in hotel / Aida Khalida Mohamed Idris... [et al.] - Mohamed Idris, Aida Khalida; Mohd Noor, Noorfarhana; Tarmazi, Siti Anis Adilah; Hashim, Norliana; Ghazali, Norfadzliana (Universiti Teknologi MARA, Negeri Sembilan, 2017)
This study seeks to analyse the factors that influence frontline employee behaviour towards guest satisfaction as frontline employee is the first person that any hotel guest would refer to should there be any queries. Thus, being a frontline employee will have an impact on guest approach and overall satisfaction. For this paper, in order to achieve the objective of the study, a review on data collected from secondary data such as journals, articles and websites were carried out. The finding of the study has proven that there is a relationship between the variables and has an impact on the service encounter. In conclusion, frontline employee behaviour is a vital factor to focus as they can give great effect on overall satisfaction or dissatisfaction for guest in their experience during their stay in the hotel.